2015
DOI: 10.5194/angeo-33-63-2015
|View full text |Cite
|
Sign up to set email alerts
|

Dipolarization fronts in the near-Earth space and substorm dynamics

Abstract: Abstract. During magnetospheric substorms and plasma transport in the Earth's magnetotail various magnetic structures can be detected. Dipolarization fronts and flux ropes are the most prominent structures characteristic for substorm dynamics. However, they are treated as separate magnetotail features independent of each other. In this paper, we analyze a number of dipolarization fronts observed by the THEMIS (Time History of Events and Macroscale Interactions during Substorms) spacecraft at different geocentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 63 publications
4
22
1
Order By: Relevance
“…This suggest that the re‐reconnecting current sheet most likely has a small‐scale, nonplanar geometry, which seems to be captured very well by the simulations. The agreement between our results, the magnetic field signatures of the dissipating flux rope‐dipolarization front scenario proposed by Slavin, Lepping, Gjerloev, Fairfield, et al (), Vogiatzis et al (), and Lu, Lu, et al (), and the re‐reconnection signatures shown in Lu et al () PIC simulations lead us to the conclusion that MMS indeed observed a dissipating flux rope associated with dipolarization front as we now discuss.…”
Section: Fields and Plasma Signatures Of Re‐reconnection X‐linesupporting
confidence: 90%
See 1 more Smart Citation
“…This suggest that the re‐reconnecting current sheet most likely has a small‐scale, nonplanar geometry, which seems to be captured very well by the simulations. The agreement between our results, the magnetic field signatures of the dissipating flux rope‐dipolarization front scenario proposed by Slavin, Lepping, Gjerloev, Fairfield, et al (), Vogiatzis et al (), and Lu, Lu, et al (), and the re‐reconnection signatures shown in Lu et al () PIC simulations lead us to the conclusion that MMS indeed observed a dissipating flux rope associated with dipolarization front as we now discuss.…”
Section: Fields and Plasma Signatures Of Re‐reconnection X‐linesupporting
confidence: 90%
“…The flux rope erosion concept proposed by Slavin, Lepping, Gjerloev, Fairfield, et al () can be applied naturally to dipolarization fronts formation by explaining the negative B Z dip, which precedes some of the dipolarization fronts. This mechanism was then reexamined by Vogiatzis et al (, ) using observations from the THEMIS spacecraft. A number of other mechanisms had also been proposed to explain this negative B Z dip feature.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2013; Forsyth et al, 2008;Fu et al, 2013;Sitnov et al, 2013;Vogiatzis et al, 2015). Analogous DF-like structures have also been observed at Mercury and Jupiter (Kronberg et al, 2005;Sundberg et al, 2012;Sun et al, 2015), suggesting that this structure may be common in all planetary magnetotails.…”
Section: Z H Yao Et Al: Dipolarization Front Current Systemmentioning
confidence: 65%
“…Seven flux ropes are tailward traveling (TFRs), and the other 18 are earthward traveling (EFRs). The few events with b n max largely deviating from theb z GSM are mostly EFRs, which could be deformed due to the strong dipole magnetic field ; see also, Lu et al, 2015;Vogiatzis et al, 2015). Figures 4a and 4c show distributions of b n max and b n min with flux rope locations in the planes of b X GSM -b Z GSM and b X GSM -b Y GSM , respectively.…”
Section: Statistical Resultsmentioning
confidence: 99%